Convergence of cMyc and β‐catenin on Tcf7l1 enables endoderm specification. (16th December 2015) - Morrison, Gillian; Scognamiglio, Roberta; Trumpp, Andreas; Smith, Austin
Abstract: The molecular machinery that directs formation of definitive endoderm from pluripotent stem cells is not well understood. Wnt/β‐catenin and Nodal signalling have been implicated, but the requirements for lineage specification remain incompletely defined. Here, we demonstrate a potent effect of inhibiting glycogen synthase kinase 3 (GSK3) on definitive endoderm production. We find that downstream of GSK3 inhibition, elevated cMyc and β‐catenin act in parallel to reduce transcription and DNA binding, respectively, of the transcriptional repressor Tcf7l1. Tcf7l1 represses FoxA2, a pioneer factor for endoderm specification. Deletion of Tcf7l1 is sufficient to allow upregulation of FoxA2 in the presence of Activin. In wild‐type cells, cMyc contributes by reducing Tcf7l1 mRNA, while β‐catenin acts on Tcf7l1 protein. GSK3 inhibition is further required for consolidation of endodermal fate via upregulation of Sox17, highlighting sequential roles for Wnt signalling. The identification of a cMyc/β‐catenin‐Tcf7l1‐FoxA2 axis reveals a de‐repression mechanism underlying endoderm induction that may be recapitulated in other developmental and patho‐logical contexts. Synopsis: Induction of definitive endoderm requires inhibition of GSK3 to trigger parallel Myc and β‐catenin‐dependent repression of Tcf7l1. GSK3 inhibition promotes endoderm induction through repression of Tcf7l1. The key endodermal gene FoxA2 is directly repressed by Tcf7l1. GSK3 inhibition elevates Myc and β‐catenin that converge to repress Tcf7l1. β‐catenin also induces Sox17 to consolidate definitive endoderm lineage commitment. Abstract : Induction of definitive endoderm during mammalian development requires inhibition of GSK3 to trigger parallel cMyc and β‐catenin‐dependent repression of the transcriptional repressor Tcf7l1.